The Impact of Prolonged Conflict on Yemen’s Agricultural Sector: A Longitudinal Analysis of Economic and Labor Dynamics (1961–2021) - Abdullah, Muqbel Ahmed Muqbel; Dokuzlu, Sertaç (Journal of Economic, Administrative and Legal Sciences, 2025)
Yemen’s agricultural sector, a cornerstone of livelihoods and food security, has endured severe disruptions from decades of conflict. Despite its critical role, no longitudinal study has systematically analyzed how protracted war (1961–2021) reshaped its economic and labor dynamics, a gap this study addresses. Using time-series data from FAO, World Bank, and Yemeni Ministry of Agriculture, we applied F-tests, autocorrelation, and linear regression models (SPSS v.26) to assess trends in agricultural GDP, labor absorption, and land use. Results reveal a 20.02% decline in cultivated areas post-2015, with agricultural GDP contribution dropping from 17% (pre-2015) to 9% (2021). Paradoxically, livestock production surged by 43% (2015–2021), highlighting adaptive resilience. The workforce reliant on agriculture remained stable at 24–28%, underscoring its role as a social safety net. These findings urge policymakers to prioritize conflict-sensitive agricultural investments, such as drought-resistant crops and decentralized cooperatives, to mitigate food insecurity. This study provides the first comprehensive empirical baseline for post-conflict recovery strategies in Yemen.
Keywords: Agricultural resilience; labor dynamics; Yemen conflicts; economic impact analysis; food security; longitudinal study